2019
DOI: 10.1021/acsabm.9b00749
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Biodegradable Multimodal Mammography Marker

Abstract: Introducing temporary markers for imaging studies is an idea, which in the proper clinical settings can be advantageous for patient compliance and in selected cases where a permanent marker is nondesirable. Hence, we developed injectable marker formulation using a biodegradable “pasty polymer” of poly­(ricinoleic acid-co-sebacic acid) (PSA:RA) containing iodixanol and iron oxide as contrast agents that can serve as a visual marker for the region suspected to have tumor growth. The goal of this work is to nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Each of the three polymers used in this study contained 20% Lipiodol and 0.2% w/w iron oxide based on prior studies documenting the adequate conspicuity of these concentrations on CT and MR, respectively. 10 The three polymer compounds were composed of Polymer A–PLGA 50:50, Polymer B–PLGA 75:25, and Polymer C–PCL. The polymers were formed into a rod shape of an adequate 1 mm diameter to fit into a biopsy syringe, similar to other commercially available markers used in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Each of the three polymers used in this study contained 20% Lipiodol and 0.2% w/w iron oxide based on prior studies documenting the adequate conspicuity of these concentrations on CT and MR, respectively. 10 The three polymer compounds were composed of Polymer A–PLGA 50:50, Polymer B–PLGA 75:25, and Polymer C–PCL. The polymers were formed into a rod shape of an adequate 1 mm diameter to fit into a biopsy syringe, similar to other commercially available markers used in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Recently, a biodegradable implant has been designed and formulated incorporating clinically approved, commonly used contrast agents visible at both CT (computer tomography) and MR (magnetic resonance). 10 In a preliminary in vitro and a short-term in vivo study, the visibility, shape, and degradation of these biodegradable implants containing Lipiodol (an X-ray contrast medium) were evaluated by CT, and it was concluded that this Lipiodol-containing poly(ricinoleic acid- co -sebacic acid) polymer is visible on CT, enabling polymer degradation to be potentially monitored noninvasively. 10 Visualization of this material on both ultrasound and MR has been characterized for this product to determine the optimal polymer composition for conspicuity and biodegradability in vitro and ex vivo for up to 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations